Altered Respiratory Physiology in Obesity. Issue 4 (2006) - Parameswaran, Krishnan; Todd, David C; Soth, Mark
Abstract : The major respiratory complications of obesity include a heightened demand for ventilation, elevated work of breathing, respiratory muscle inefficiency and diminished respiratory compliance. The decreased functional residual capacity and expiratory reserve volume, with a high closing volume to functional residual capacity ratio of obesity, are associated with the closure of peripheral lung units, ventilation to perfusion ratio abnormalities and hypoxemia, especially in the supine position. Conventional respiratory function tests are only mildly affected by obesity except in extreme cases. The major circulatory complications are increased total and pulmonary blood volume, high cardiac output and elevated left ventricular end-diastolic pressure. Patients with obesity commonly develop hypoventilation and sleep apnea syndromes with attenuated hypoxic and hypercapnic ventilatory responsiveness. The final result is hypoxemia, pulmonary hypertension and progressively worsening disability. Obese patients have increased dyspnea and decreased exercise capacity, which are vital to quality of life. Decreased muscle, increased joint pain and skin friction are important determinants of decreased exercise capacity, in addition to the cardiopulmonary effects of obesity. The effects of obesity on mortality in heart failure and chronic obstructive pulmonary disease have not been definitively resolved. Whether obesity contributes to asthma and airway hyper-responsiveness is uncertain. Weight reduction and physical activity are effective means of reversing the respiratory complications of obesity.